Analisa Kebutuhan dan Perancangan Sistem Informasi Penjualan Berbasis Web - Trimarsiah, Yunita (SISKOMTI: Jurnal Sistem Informasi Komputer dan Teknologi Informasi, 2022)
Aisyah shop is one of the agents engaged in the sale and purchase of basic necessities. In the process of selling and buying data processing is still done manually, namely by recording into sales and purchases notes. With these conditions, innovation is needed to increase sales so that it can simplify, speed up and increase convenience in transacting at the store, so the author makes a web-based sales information system. In the development of the system, supporting data is needed which is obtained using data collection techniques such as: observation, interviews and literature, while in the development of the system, the RAD (Rapid application Development) software development method is applied. This method is needed for making short systems. This system is designed using codeigniter and mysql framework. In the final stage of testing the system using the Black Box Testing method which shows the results that the information system built already has a good system in accordance with the needs analysis. Keywords: Online Sales Information System, RAD, Black Box Testing, Codeigniter, mysql